Garcinol in gastrointestinal cancer prevention: recent advances and future prospects - Patwa, Nitika; Chauhan, Ritu; Chauhan, Abhishek; Kumar, Manoj; Ramniwas, Seema; Mathkor, Darin Mansor; Saini, Adesh Kumar; Tuli, Hardeep Singh; Haque, Shafiul; Slama, Petr (Journal of cancer research and clinical oncology, 2024)
Gastrointestinal cancers continue to pose a significant global health challenge, with millions of new cases diagnosed each year. Despite advancements in treatment, the prognosis for many patients remains poor. This article explores the potential of garcinol, a polyisoprenylated benzophenone found in various Garcinia species, as a therapeutic agent against gastrointestinal malignancies. The objective is to review recent research on garcinol's anticancer properties, its mechanisms of action, and safety aspects. Garcinol exhibits anticancer effects in esophageal, gastric, colorectal, pancreatic, and liver cancers by inhibiting metastasis, inducing apoptosis, and targeting key molecular pathways in cancer progression. Nanotechnology is explored as a means to enhance garcinol delivery and efficacy. Safety assessments suggest a promising toxicity profile. Garcinol shows significant potential as a natural therapeutic agent for gastrointestinal cancers, and future research is needed on optimizing its delivery, exploring synergistic combinations, and conducting clinical trials to validate its efficacy and safety for clinical applications.
Keywords: Gastrointestinal cancers; Antineoplastic Agents, Phytogenic; terpeny; zvířata; Humans; fytogenní protinádorové látky; Pharmacokinetics; lidé; Gastrointestinal Neoplasms; Targeted therapy; Garcinol; gastrointestinální nádory; Terpenes; Apoptosis; Animals